Survey Tingkat Trust dan Rapport Konselor sebagai Wujud Konselor yang Efektif Berdasarkan Perspektif Siswa - Nisa, Lilis Choirunnatun; Supriyo, Adetea Apriliyanti; Muwakhidah; Leeuwanda, Adetea AprInneke; Putra, MuwakIrwan Yogaswara; Laily, Widiya Nur (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research aims to determine the level or profile of trust and rapport as a form of effective counselor based on the student's perspective. The method used by researchers is quantitative with a descriptive design and survey approach. The number of samples used was 60 students from SMA Hang Tuah 2 Sidoarjo. The sampling technique used is random sampling. This research instrument uses a trust and rapport questionnaire. The data analysis technique uses descriptive percentages. The research results show that trust is very important, if trust cannot be built well then the counseling relationship cannot be established well. Meanwhile, rapport needs to be built to create warmth and comfort between the counselor and the counselee.